2011
DOI: 10.1007/s00394-011-0182-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary d-limonene alleviates insulin resistance and oxidative stress–induced liver injury in high-fat diet and L-NAME-treated rats

Abstract: These data provide new insights into the therapeutic approach of d-limonene against the development of the metabolic syndrome associated with NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(24 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…, Table ). Among them, camphene was reported to reduce plasma cholesterol and triglycerides in hyperlipidemic rats (Vallianou et al , ) and also other essential oils including limonene (Abdollahi et al , ; Victor Antony Santiago et al , ) are known to exert hypolipidemic activity. Thus, our GC‐MS data support that EOPK, an essential oil mixture, exerts antihyperlipidemic activity in HepG2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…, Table ). Among them, camphene was reported to reduce plasma cholesterol and triglycerides in hyperlipidemic rats (Vallianou et al , ) and also other essential oils including limonene (Abdollahi et al , ; Victor Antony Santiago et al , ) are known to exert hypolipidemic activity. Thus, our GC‐MS data support that EOPK, an essential oil mixture, exerts antihyperlipidemic activity in HepG2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Considering its anticancer activity, the aim of this study was to develop solid lipid nanoparticles (SLNs) for (+)-limonene 1,2-epoxide (Lim-SLNs), and test the effect of the particles on the release profile, antioxidant activity, and cytotoxicity in a keratinocyte cell line. Several reports confirm that (+)-limonene 1,2-epoxide can induce tumor cell apoptosis, as well as suppression of the PI3K/Akt/mTOR17 and NF-κB pathways [39]. Phase I clinical trials have been reported by Vigushin et al for this monoterpene derivative [40].…”
Section: Introductionmentioning
confidence: 89%
“…Monoterpenes such as limonene, and menthol consist of two isoprene units, and are major constituent of essential oils obtained from citrus fruits, cherries, spearmint dill, caraway, apricots and grapes. Rats supplemented with d-limonene result in reduced highfat diet-induced hepatic lipid level, lipid peroxidation, increased phase II enzymes activities, and decreased liver and pancreas pathology that against metabolic syndrome [159] (Table 3). Menthol is found to suppress bone resorption by inhibition of osteoclastogenesis via interfere with RANKL signaling [160].…”
Section: Terpenoidsmentioning
confidence: 98%